Medicinal dietary plants of the Yi in Mile, Yunnan, China - Jingxian Sun; Yong Xiong; Yanhong Li; Qingsong Yang; Yijian Chen; Mengyuan Jiang; Yukui Li; Hongrui Li; Zizhen Bi; Xiangzhong Huang; Shugang Lu (BMC, 2020)
Abstract Background The Yi is the largest ethnic group in Yunnan Province (China), with a population of five million. The Yi people tend to live in mountainous areas, and their culture includes a unique dietary system for treating and protecting people against illnesses. Medicinal plants occupy an essential place in the Yi diet because they play a key role in health and the prevention and treatment of diseases. However, few studies have addressed these medicinal dietary plants and their importance in the Yi's daily lives. The aim of this study was to (1) investigate the medicinal dietary plants used by the Yi in Mile City, (2) document the traditional knowledge held about these plants, (3) identify species with important cultural significance to the Yi in Mile City, and (4) analyze the special preparation methods and consumption habits of these plants. Methods Field investigations were performed in six villages in Mile City, Honghe Hani and Yi Autonomous Prefecture, Yunnan, from July 2017 to May 2018. Information was collected using direct observation, semi-structured interviews, key informant interviews, individual discussions, and focus group discussions. The use value (UV) and frequency of utilization index (FUI) of these plants were analyzed. Plant samples and voucher specimens were collected for taxonomic identification. Results This study documented 124 species belonging to 62 families and 102 genera. These plants included angiosperms (117 spp.), gymnosperms (3), pteridophytes (2), lichen (1), and fungus (1). The 20 species with the highest UV were noted as being particularly important to the Yi people's daily life in Mile City. The primary medicinal preparation method for plants recorded in the study was decoction. The most commonly used plant parts were fruits and roots. The most frequently used edible parts were fruits, and the most frequently used medicinal parts were roots. The medicinal parts were used to treat diseases such as rheumatism, edemas, kidney deficiency, spleen deficiency, gastritis, parasites, and so on. Conclusion A wide variety of medicinal dietary plants are used by the Yi people in Mile City. Those plants, which have both rich nutritional and medicinal value, occupy an essential part of the Yi dietary and medicine culture. Ethnobotanical surveys of medicinal dietary plants provide a theoretical reference for the conservation and sustainable use of the plant resources and could contribute to the protection of the Yi food culture and traditional medicine in Mile City. In addition, this information provides a sound basis for developing and using Yi ethnic medicine and health products.